1951
DOI: 10.2307/1943559
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation and Habitats in a Southwestern Volcanic Area

Abstract: Bureau loaned an i~strument shelter and rain gage. Thanks ll:O to the officials and staff of the Nava io Fluorsnar Mine, particularly Mr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1954
1954
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…It would be expected to occur lower altitudinally as it occurred farther north but such is not the case. These facts agree with the observation of Lindsey ( 1951) that J. pachyphloea is influenced to a high degree by the substrate, as opposed to the climatic factor.…”
Section: Differential Moisture Requirementssupporting
confidence: 92%
“…It would be expected to occur lower altitudinally as it occurred farther north but such is not the case. These facts agree with the observation of Lindsey ( 1951) that J. pachyphloea is influenced to a high degree by the substrate, as opposed to the climatic factor.…”
Section: Differential Moisture Requirementssupporting
confidence: 92%
“…This paradox may result because of minimal ground-flora competition, deep subsoils (> 1.5 m) consisting of alternating cinder-soil layers retaining subsoil moisture, or loose soils facilitating development of extensive, branched root systems (Haasis, 1921). Colton (1932) also noted that rapid diameter growth occurred on black cinder soils near Sunset Crater in the study area, and Lindsey (1951) found that the greatest mean increment of 3.4 mm year )1 among central New Mexico soils he studied occurred on volcanic cinder soils.…”
Section: Pinus Ponderosa Growthmentioning
confidence: 86%
“…The unique vegetation communities found on the lava flows at El Malpais were first described by Lindsey (1951), including the stunted slow-growing conifers. The sparsely vegetated and forbidding lava-rock terrain has been protected from grazing, logging, and other human impacts (Fig.…”
Section: Study Areamentioning
confidence: 99%